A Legal Responsibility of a Notary for Actions Performed by Parties in the Making an Authentic Ded - T. Riza Zarzani; Onny Medaline; Dartimnov Dartimnov (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The purpose of this study was to determine the position of a notary in making an authentic deed, the form of a notary's responsibility for violations of the UUJN in creating an original act and the effectiveness of sanctions for a notary who violates the UUJN in doing an authentic deed. The writing of this thesis research methodology uses normative juridical research methods using an empirical juridical approach, with qualitative analysis. Qualitative analysis means that research results do not depend on the amount of data based on numbers, but data analysed is carried out in-depth and holistically. Based on the research results, it is known that the position of a notary in doing an authentic deed is regulated explicitly in Article 15 paragraphs (1), (2), and (3) of Law Number 30 of 2004 Jo. Law Number 2 of 2014 concerning the Position of Notary consists of general, special and future authorities. In its implementation, the form of a notary's liability that violates the UUJN in doing an authentic deed is divided into 2 (two) states, first: a civil notary liability of a notary because a notary violates the provisions of Article 84 of Law No. cancel or nullify by law, secondly: administrative liability of the notary occurs because in doing an authentic deed the notary does not heed Article 84 of Law Number 30 of 2004 concerning the position of a notary, for this violator with the threat of the heaviest penalty the notary can be dismissed from his position.